INVESTIGATION OF DATA PROCESSING FOR PASSIVE ACCOUSTIC AND ELECTROMAGNETIC UNDERWATER LOCALISATION AND CLASSIFICATION - JAWAHAR A; RAJYA LAKSHMI CH (Innovare Journal of Engineering and Technology, 2017)
In our earlier work, data fusion with specific application to underwater tracking environment is explored. The target can be tracked using array bearings, while it is moving with constant velocity and maneuvering occasionally. In this paper, it is shown that if data fusion is carried out using the bearing measurements available from Towed Array (TA) along with hull mounted array‟s bearings, then tracking of a continuously moving target can be carried out easily. This algorithm is independent of ownship maneuver for the observability of the process. Song and Speyer's & Galkowski and Islam‟s modified gain algorithms are utilized with some modifications for estimation. Monte Carlo simulation is performed and results are shown for various typical geometries.